2003
DOI: 10.1038/oby.2003.31
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Eating, Alexithymia, and Binge‐Eating Disorder in Obese Women

Abstract: PINAQUY, SANDRINE, HENRI CHABROL, CHANTAL SIMON, JEAN-PIERRE LOUVET, AND PIERRE BARBE. Emotional eating, alexithymia, and binge-eating disorder in obese women. Obes Res. 2003;11:195-201. Objective: To investigate the relationships between alexithymia and emotional eating in obese women with or without Binge Eating Disorder (BED). Research Methods and Procedures:One hundred sixtynine obese women completed self-report questionnaires, including the Beck Depression Inventory, the State Trait Anxiety Inventory, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
172
1
18

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(220 citation statements)
references
References 35 publications
15
172
1
18
Order By: Relevance
“…Problems identifying and expressing emotions make it more difficult for patients with a BED to cope with negative emotions and psychosocial stress. 51 This was supported in the present study by a lower mood rating in reaction to the mental stress tasks. Parasympathetic cardiac regulation during stress has received considerable attention as a physiological marker for emotional processing and self-regulation in recent years.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Problems identifying and expressing emotions make it more difficult for patients with a BED to cope with negative emotions and psychosocial stress. 51 This was supported in the present study by a lower mood rating in reaction to the mental stress tasks. Parasympathetic cardiac regulation during stress has received considerable attention as a physiological marker for emotional processing and self-regulation in recent years.…”
Section: Discussionsupporting
confidence: 76%
“…Individuals who engage in binge eating appraise challenging situations as more stressful and show greater difficulties managing the emotional consequences of stress, in comparison to subjects without an eating disorder. 4 As in patients with BN, the relationship between negative mood and binge eating pathology has also been reported for individuals with a BED. [5][6][7] Psychophysiological research has greatly advanced our understanding of the importance of the parasympathetic nervous system, in addition to the sympathetic branch, in stress and emotional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Based on results of earlier studies, it was hypothesized that eatingdisordered women, compared to non-eating-disordered women, would report higher levels of negative affect and emotional eating (e.g., Bekker & Boselie, 2002;Cooper & Hunt, 1998;Pinaquy, Chabrol, Simon, Louvet, & Barbe, 2003) and would also score higher on assessment instruments of emotion-oriented coping and avoidance coping strategies (e.g., Kenardy, Arnow, & Agras, 1996;Nagata, Matsuyama, Kiriike, Iketani, & Oshima, 2000;Yager, Rorty, & Rossotto, 1995).…”
Section: Article In Pressmentioning
confidence: 99%
“…However, this differs for various subgroups within the obese population, such as those seeking treatment, those with co-morbid binge eating and poor body image and those with severe levels of obesity, all whom experience higher levels of psychological distress. [15][16][17][18] Many previous studies on the interface between weight and EDs have relied on treatment seeking, often small clinical samples of people with obesity, for example, 15,[9][10][11][12][13][14][15][16][17][18][19][20][21][22] or have focused on BED [20][21][22][23][24][25][26][27] or ED behaviours only. 4 They have found that binge eating contributes to obesity, that obese people with BED have higher depression, anxiety, eating and weight concerns and poorer quality of life than in other obese subjects; also that poor body image evaluation and negative self schemas relate to depression in obese people and that body image beliefs relate to level of obesity (heavier women are less satisfied with appearance).…”
Section: Introductionmentioning
confidence: 99%